Flexible Analog Front Ends of Reconfigurable Radios Based on Sampling and Reconstruction with Internal Filtering - Poberezhskiy Yefim S.; Poberezhskiy Gennady Y. (EURASIP Journal on Wireless Communications and Networking, 2005)
Bandpass sampling, reconstruction, and antialiasing filtering in analog front ends potentially provide the best performance of software defined radios. However, conventional techniques used for these procedures limit reconfigurability and adaptivity of the radios, complicate integrated circuit implementation, and preclude achieving potential performance. Novel sampling and reconstruction techniques with internal filtering eliminate these drawbacks and provide many additional advantages. Several ways to overcome the challenges of practical realization and implementation of these techniques are proposed and analyzed. The impact of sampling and reconstruction with internal filtering on the analog front end architectures and capabilities of software defined radios is discussed.